Identifikasi Sistem Pengendalian Kualitas Proses Pengolahan Kelapa Sawit dengan Menggunakan Deming’s View Production System - M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
The productivity of a palm oil mill is not only seen from how many CPO that can be produced, but also be seen from the efficiency of the process. Therefore it is necessary to control the quality of the processing of palm oil itself, which includes the quality of raw materials, processes, and quality products. Thus each company can easily evaluate the performance of each of the quality object and can easily identify any deviations. Identification of palm oil processing system in palm oil mill can be done by using a diagram called the Deming's view production system. Thus the object will be seen clearly what should be observed in the palm oil processing to be able to produce a treatment system that meets the quality standards set by the company, both on the input, process and output. By using the 5W+H principle as an analysis of the system will be identified on the objects depicted in the Deming's view of the production system diagram. The result is an overview of how to take measurements of the quality parameters of the process and what targets to be achieved in the process.